Edukasi Kesehatan Reproduksi bagi Remaja Putri untuk Mencegah Kehamilan Tidak Diinginkan - Marpaung, Sastrika Handayani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Unwanted pregnancy among adolescent girls remains a significant public health issue with serious impacts on physical, psychological, social, and economic aspects. Limited knowledge of reproductive health, poor decision-making skills, and environmental influences are contributing factors to this problem. This Community Service Program aimed to increase knowledge and awareness of reproductive health among adolescent girls as an effort to prevent unwanted pregnancy. The program included a pre-test, interactive lectures, group discussions, educational video screenings, leaflet distribution, and a post-test for evaluation. It was conducted in July 2025 at SMA X, Kota Y, involving 50 adolescent girls as participants. The results showed an increase in the average knowledge score from 56.2 to 75.9, representing a 35% improvement after the educational intervention. Participants demonstrated high enthusiasm, with 80% actively asking questions or sharing opinions. This program indicates that participatory-based reproductive health education can effectively improve adolescent girls’ knowledge and is expected to serve as a preventive measure to reduce the incidence of unwanted pregnancy among teenagers.